The choking game: A deadly game. Analysis of two cases of "self-strangulation" in young boys and review of the literature. (February 2015) - Re, Laura; Birkhoff, Jutta M.; Sozzi, Marta; Andrello, Luisa; Osculati, Antonio M.M.
Abstract: The choking game is defined as a self-strangulation or strangulation by another person with the hands or a noose to achieve a brief euphoric state caused by cerebral hypoxia. Death may occur, but forensic pathologists often classify them as suicides or accidental deaths, without focusing on the possibility that they may result from a deliberate self-temporary-asphyxiation, turned into a deadly game. Presenting two fatal cases of self-strangulation involving an 11-year-old boy and a teenager of 15 years, the authors identify victims' characteristics and death scene's evidence, which may help to distinguish if a death is from an asphyxial suicide or an asphyxial game. Highlights: Analysis of two cases of self-strangulation. Analysis of the most significant evidence related to this activity. Full review of the literature. Indications for a proper evaluation of cases of choking game. Indications for a proper prevention of cases of choking game.